2019
DOI: 10.1155/2019/1959082
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Pars Plana Vitrectomy with Internal Limiting Membrane Peel and Pars Plana Vitrectomy with Internal Limiting Membrane Flap Technique for Management of Traumatic Full Thickness Macular Holes

Abstract: Purpose. To compare the efficacy of PPV and ILM peel versus PPV and IFT in patients with traumatic FTMH. Methods. Retrospective interventional comparative case series including two groups of patients with traumatic FTMH. Patients were divided into group I (ILM peel) and group II (IFT). The main outcome measure was closure of the macular hole and restoration of the foveal microstructure. The independent-samples T-test and ANOVA test were used to study the mean between 2 groups and calculate the P value, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
(24 reference statements)
4
14
0
Order By: Relevance
“…Conversely, if the preoperative visual acuity is as a result of the retinal injury from the MH, the postoperative Table 2. Baseline characteristics of patients with initial surgically closed traumatic macular hole visual acuity may indeed be correlated with it, as in our study and others [12,13]. We also found the mean macular height was lower in eyes with poor postoperative visual acuity, proved by Huang et al [17] in TMHs without surgery.…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, if the preoperative visual acuity is as a result of the retinal injury from the MH, the postoperative Table 2. Baseline characteristics of patients with initial surgically closed traumatic macular hole visual acuity may indeed be correlated with it, as in our study and others [12,13]. We also found the mean macular height was lower in eyes with poor postoperative visual acuity, proved by Huang et al [17] in TMHs without surgery.…”
Section: Discussionsupporting
confidence: 86%
“…In a previously published comparative study, we reported our findings on the outcomes of comparing the modified IFT and conventional ILM peel in TMH. We found that modified IFT yielded superior hole closure rate (92% vs 75%), and better final BCVA (5 lines gain vs 2.5 lines gain) than conventional ILM peel approach 12. We acknowledge the limitations of the present study that included its retrospective design, which caused inhomogeneity of the baseline characteristics of recruited patients in terms of baseline MLD, time lapse prior to surgery, and duration of follow-up.…”
Section: Discussionmentioning
confidence: 81%
“…The surgical technique used in the present study was described in detail in a previous publication 12. Briefly the technique consisted of standard 3-port 23-gauge PPV and posterior hyaloid dissection (PHD), followed by modified ILM flap technique (IFT).…”
Section: Methodsmentioning
confidence: 99%
“…18 Ghoraba et al showed inverted flap group has a significantly better anatomic and functional outcome than ILM peel in traumatic FTMH. 19…”
Section: Discussionmentioning
confidence: 99%